Agony and the ecstasy - Reed, Carol, 1906-1976; Dunne, Philip, 1908-1992; Heston, Charlton; Harrison, Rex; Cilento, Diane; Andrews, Harry, 1911-1989; Lupo, Alberto, 1924-1984; Celi, Adolfo, 1922-1986; Venantini, Venantino, 1930-; Stacy, John, 1914-1988; Tozzi, Fausto, 1921-1978; Audley, Maxine; et al. (Beverly Hills, California Twentieth Century Fox Home Entertainment, 2014)
In this historical drama, when Pope Julius II commissions Michelangelo to paint the ceiling of the Sistine Chapel, the artist initially refuses. Virtually forced to do the job by Julius, he later destroys his own work and flees Rome. Eventually resumed, the project becomes a battle of wills fueled by the artistic and temperamental differences between the two men.
Wide screen (2.20:1).
Based on the novel "The agony and the ecstasy" by Irving Stone.
Originally released as a motion picture in 1965.
Special features: Restoration comparison; Teaser; Trailer.
Music composed and conducted by Alex North ; director of photography, Leon Shamroy ; art direction, Jack Martin Smith ; production designed by John DeCuir ; choral music composed and conducted by Franco Potenza ; film editor, Samuel E. Beetley ; set decorations, Dario Simoni ; costumes designed by Vittorio Nino Novarese ; orchestration, Alexander Courage.
Charlton Heston, Rex Harrison, Diane Cilento, Harry Andrews, Alberto Lupo, Adolfo Celi, Venantino Venantini, John Stacy, Fausto Tozzi, Maxine Audley, Tomas Milian.
Keywords: Julius -- II, -- Pope, -- 1443-1513 -- Drama; Michelangelo Buonarroti, -- 1475-1564 -- Drama; Stone, Irving, -- 1903-1989 -- Film adaptations; Cappella Sistina (Vatican Palace, Vatican City) -- Drama; Mural painting and decoration, Renaissance -- Vatican City -- Drama; Artists -- Italy -- Drama; Drama; Feature films; Fiction films; Film adaptations; Historical films; Video recordings for the hearing impaired